Using a Seismic Dilatometer to Identify Collapsible Soils - Rocha, Breno Padovezi; de Carvalho Rodrigues, André Luís [UNESP]; Rodrigues, Roger Augusto [UNESP]; Giacheti, Heraldo Luiz [UNESP] (Springer Nature, 2021)
Collapsible soils are unusual geomaterials found in several regions of the world. These soils undergo sudden and large volumetric compressive deformations upon wetting under constant loading. It is a problematic soil that must be identified in the first step of a site investigation. The seismic flat dilatometer (SDMT) has been used by the geotechnical community as a logging tool for site characterization. It provides several parameters and can be used to identify collapsible soil. A database with in situ and laboratory tests at 24 sites where collapsible and noncollapsible soils occurred was assembled. Seismic flat dilatometer (SDMT), flat dilatometer (DMT) and seismic data were reviewed and interpreted to define a qualitative approach to identify collapsible soils using the maximum shear modulus (G0), constrained modulus (MDMT), material index (ID) and horizontal stress index (KD). In the database of investigated soils, collapsible soils were found to have G0/MDMT values above 10 and KD values below 4, while noncollapsible soils had G0/MDMT values below 10 and KD values above 4. Collapsible soils show an increase in G0/MDMT when ID increases, while the opposite occurs for noncollapsible soils. The G0/MDMT versus KD chart and boundaries were used to differentiate between collapsible and noncollapsible soils. This qualitative approach is intended to be used during preliminary investigation to identify potentially collapsible soils and select those to be tested in the laboratory.
Keywords: Collapsible soils; G0/MDMT; Identification; Intermediate parameters; Seismic dilatometer; Small-strain stiffness